(untitled) (Journal of Scientific Research, 2016)
2’,4’,5’- and 2’,3’,4’-trimethoxy flavanones have been synthesized starting with 2-hydroxyacetophone and substituted aldehyde. Antibacterial activities of the flavanones have been tested along with their corresponding chalcones against two human pathogenic bacteria (Streptococcus-b-haemolyticus and Klebsiella sp. (G-)). Antifungal activities of the flavanones have also been investigated against two plants pathogenic mold fungi (Rhizactonia solani Sclerotium rolfsii). The structures of the synthesized compounds have been characterized with the help of UV, IR and 1H NMR and 13C-NMR spectra. The antibacterial and antifungal screening were performed in vitro by the filter paper disc diffusion method and poisoned food technique. The flavanones showed antibacterial activity while no activity was observed to their corresponding chalcones against the tested bacteria. On the other hand, chalcones and their corresponding flavanones both showed fungicidal activities.